Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized for You

we will pick new questions that match your level based on your Timer History

Track Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

It appears that you are browsing the GMAT Club forum unregistered!

Signing up is free, quick, and confidential.
Join other 500,000 members and get the full benefits of GMAT Club

Registration gives you:

Tests

Take 11 tests and quizzes from GMAT Club and leading GMAT prep companies such as Manhattan GMAT,
Knewton, and others. All are free for GMAT Club members.

Applicant Stats

View detailed applicant stats such as GPA, GMAT score, work experience, location, application
status, and more

Books/Downloads

Download thousands of study notes,
question collections, GMAT Club’s
Grammar and Math books.
All are free!

Thank you for using the timer!
We noticed you are actually not timing your practice. Click the START button first next time you use the timer.
There are many benefits to timing your practice, including:

1. tells us that a = 0 or 2. INSUFFICIENT 2. since (a+b)^2 = (a^2+2ab+b^2) the whole fraction = 1. 1-1 = 0 and (b/c) = 0 so b must be 0. as long as one of the 3 integers is 0 abc will = 0 as well

Thanks. I understood why statement 1 didn't work but couldn't figure out how statement 2 lead to B=0.

Now I get it. [b/c] = 0, where c cannot = 0 (given), so b must =0. I kept thinking [b/c] must =1 and forgot to take into account the last part that says [b/c] actually equals 0.

1) a^2 = 2a 2) (b/c) = [[(a+b)^2] / [a^2 + 2ab + b^2]] - 1; where a does not equal -b and c does not equal 0;

Statement (1) ALONE is sufficient, but Statement (2) ALONE is not sufficient Statement (2) ALONE is sufficient, but Statement (1) ALONE is not sufficient BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient EACH statement ALONE is sufficient Statements (1) and (2) TOGETHER are NOT sufficient

Answer is B Statement 1: does not give any information about a.b.c---> Insufficient Statement 2: Can be rewrite as b/c = [(a+b)^2/(a+b)^2]-1 b/c = 1-1 = 0 which gives product of a,b and c is zero. Hence Sufficient

I saw this question in a gmat club test, and I still have some doubts about the answer.

How can i reduce the expresion [(a+b)^2/(a+b)^2], if we don't know whether (a+b)^2 is 0 or not. ¿??

Thanks in advance for your help!

BELOW IS REVISED VERSION OF THIS QUESTION:

Is \(abc = 0\) ?

In order \(abc = 0\) to be true at least one of the unknowns must be zero.

(1) \(a^2 = 2a\) --> \(a^2-2a=0\) --> \(a(a-2)=0\) --> \(a=0\) or \(a=2\). If \(a=0\) then the answer is YES but if \(a=2\) then \(abc\) may not be equal to zero (for example consider: \(a=2\), \(b=3\) and \(c=4\)). Not sufficient.

If a+b were equal 0, then \(\frac{c*(a+b)^2}{(a+b)^2}\) would be undefined and \(b= \frac{c*(a+b)^2}{(a+b)^2} - c\) (which is given as a true statement) wouldn't make sense.

Happy New Year everyone! Before I get started on this post, and well, restarted on this blog in general, I wanted to mention something. For the past several months...

It’s quickly approaching two years since I last wrote anything on this blog. A lot has happened since then. When I last posted, I had just gotten back from...

Post-MBA I became very intrigued by how senior leaders navigated their career progression. It was also at this time that I realized I learned nothing about this during my...